High Mobility Group Box 1 in Pig Amniotic Membrane Experimentally Infected with E. coli O55 - Igor Splichal; Alla Splichalova (Biomolecules, 2021)
Intra-amniotic infections (IAI) are one of the reasons for preterm birth. High mobility group box 1 (HMGB1) is a nuclear protein with various physiological functions, including tissue healing. Its excessive extracellular release potentiates inflammatory reaction and can revert its action from beneficial to detrimental. We infected the amniotic fluid of a pig on the 80th day of gestation with 1 × 104 colony forming units (CFUs) of E. coli O55 for 10 h, and evaluated the appearance of HMGB1, receptor for glycation endproducts (RAGE), and Toll-like receptor (TLR) 4 in the amniotic membrane and fluid. Sham-infected amniotic fluid served as a control. The expression and release of HMGB1 were evaluated by Real-Time PCR, immunofluorescence, immunohistochemistry, and ELISA. The infection downregulated HMGB1 mRNA expression in the amniotic membrane, changed the distribution of HMGB1 protein in the amniotic membrane, and increased its level in amniotic fluid. All RAGE mRNA, protein expression in the amniotic membrane, and soluble RAGE level in the amniotic fluid were downregulated. TLR4 mRNA and protein expression and soluble TLR4 were all upregulated. HMGB1 is a potential target for therapy to suppress the exaggerated inflammatory response. This controlled expression and release can, in some cases, prevent the preterm birth of vulnerable infants. Studies on suitable animal models can contribute to the development of appropriate therapy.